The relationship between family support and the implementation of Early Breastfeeding Initiation (IMD) at PKU Muhammadiyah Mojoagung Hospital Jombang Regency - Mudhawaroh Mudhawaroh; Septi Fitrah Ningtyas; Chanda Paramitha Bherty; Kolifah Kolifah; Niken Grah Prihartanti (Science Midwifery, 2023)
Early Breastfeeding Initiation (IMD) is an important aspect in the care period for mothers and newborns. In this case, family support has a very important role, and can support the implementation of early breastfeeding initiation. The purpose of this research is to identify and examine the association between family support and the beginning, maintenance, and development of breastfeeding in moms who have recently had a cesarean section. This study collects data using a quantitative research design and cross-sectional methodology by use of questionnaires and observation. Forty postpartum moms who underwent cesarean sections at PKU Muhammadiyah Hospital in Mojoagung, Jombang Regency, participated in the study. Statistical software was used to analyse and analyze the data through the Chi-square test. Early breastfeeding is associated with higher levels of family support, as shown by a p value of 0.024 (where the value is 0.05) and a significance level of 0.05. Within an hour after giving birth, 23 of the women who had family support were able to do IMD, but just 2 of the women who did not have family support were able to. Early breastfeeding in postpartum women may be more likely if they have strong family support. This support can take the form of emotional support, information and physical assistance in helping mothers to initiate early breastfeeding. Therefore, the role of the family in providing adequate support from the start of labor is very important to improve IMD practices and provide optimal health benefits for the baby.